Correlated organic–inorganic motion enhances stability and charge carrier lifetime in mixed halide perovskites. Issue 12 (8th March 2022) - Zhao, Xi; Lu, Haoran; Fang, Wei-Hai; Long, Run
Abstract : Correlated organic–inorganic motion delays nonradiative electron–hole recombination and improves the stability of FAPbI3 upon Br doping. Abstract : Organic cations are believed to have little influence on the charge carrier lifetime in hybrid organic–inorganic perovskites. Experiments defy this expectation. We consider formamidinium lead iodide (FAPbI3 ) doping with and without Br as two prototypical systems, and perform ab initio time-domain nonadiabatic (NA) molecular dynamics simulations to investigate nonradiative electron–hole recombination. The simulations demonstrate that correlated organic–inorganic motion stabilizes the lattice and inhibits nonradiative charge recombination in FAPbI3 upon Br doping. Br doping suppresses the rotation of FA and the vibrations of both organic and inorganic components, and leads to hole localization and the extent of localization is enhanced upon thermal impact, notably reducing the NA coupling by decreasing the overlap between the electron and hole wave functions. Doping also slightly increases the bandgap for further decreasing NA coupling and enhances the open-circuit voltage of perovskite solar cells. The small NA coupling and large bandgap beat the slow coherence loss, delaying electron–hole recombination and extending the charge carrier lifetime to 1.5 ns in Br-doped FAPbI3, which is on the order of 1.1 ns in pristine FAPbI3 . The obtained time scales are in good agreement with experiments. Multiple phonon modes, including those of both the inorganic and organic components, couple to the electronic subsystem and accommodate the excess electronic energy lost during nonradiative charge recombination. The study reveals the unexpected atomistic mechanisms for the reduction of electron–hole recombination upon Br doping, rationalizes the experiments, and advances our understanding of the excited-state dynamics of perovskite solar cells.